Sevoflurane protects against cerebral ischemia/reperfusion injury via microrna-30c-5p modulating homeodomain-interacting protein kinase 1. Issue 2 (20th December 2021) - Su, Guoning; Qu, Yan; Li, Gang; Deng, Min
ABSTRACT: Sevoflurane (SEV) has been reported to be an effective neuroprotective agent for cerebral ischemia/reperfusion injury (CIRI). However, the precise molecular mechanisms of Sev preconditioning in CIRI remain largely unknown. Therefore, CIRI model was established via middle cerebral artery occlusion method. SEV was applied before modeling. after successful modeling, lentivirus was injected into the lateral ventricle of the brain. Neurological impairment score was performed in each group, and histopathologic condition, infarct volume, apoptosis, inflammation, oxidative stress, microRNA (miR)-30 c-5p and homeodomain-interacting protein kinase 1 (HIPK1) were detected. Mouse hippocampal neuronal cell line HT22 cells were pretreated with SEV, and the in vitro model was stimulated via oxygen-glucose deprivation and reoxygenation. The corresponding plasmids were transfected, and the cell growth was detected, including inflammation and oxidative stress, etc. The targeting of miR-30 c-5p with HIPK1 was examined. The results clarified that reduced miR-30 c-5p and elevated HIPK1 were manifested in CIRI. SEV could improve CIRI and modulate the miR-30 c-5p-HIPK1 axis in vitro and in vivo, and miR-30 c-5p could target HIPK1. Depressed miR-30 c-5p could eliminate the protection of SEV in vitro and in vivo . Repression of HIPK1 reversed the effect of reduced miR-30 c-5p on CIRI. Therefore, it is concluded that SEV is available to depress CIRI via targeting HIPK1 through upregulated miR-30 c-5p.